2005
DOI: 10.3233/nre-2005-20207
|View full text |Cite
|
Sign up to set email alerts
|

Language outcomes subsequent to treatment of brainstem tumour in childhood

Abstract: While the occurrence and management of brainstem tumours in children would not traditionally indicate potential direct structural impact on classical language centres, recent theories have implicated some involvement of the brainstem in a functional language and cognitive neural loop between the cerebellum and the cerebral hemispheres. Thus, the present paper explored the impact of treatment for brainstem tumour on the general and high-level language abilities of six children treated for brainstem tumour, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A number of studies on language outcomes included between‐group comparisons with a typically developing control group and found no statistically significant differences between groups on some or all measures 25,26,28,69,74,75,77–79,83–85 . However, the ability to interpret group‐level comparisons was often limited due to small sample sizes for the CBTL group (≤17).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies on language outcomes included between‐group comparisons with a typically developing control group and found no statistically significant differences between groups on some or all measures 25,26,28,69,74,75,77–79,83–85 . However, the ability to interpret group‐level comparisons was often limited due to small sample sizes for the CBTL group (≤17).…”
Section: Resultsmentioning
confidence: 99%
“…However, the ability to interpret group‐level comparisons was often limited due to small sample sizes for the CBTL group (≤17). The majority of these studies also included an individual‐level analysis and descriptively reported language outcomes, revealing difficulties in some, but not all, children with CBTL 25,26,28,69,74,75,77–79,83 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations